(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
World demand for paper is increasing. Short rotation pulpwood is needed. Sesbania grandiflora also known as Turi, is a fast growing and straight log species. The scholarly information of Turi as pulpwood are still limited. This paper aims to provide information of sodium hydroxide effect on the paper made from pulp derived from Turi. Sodium hydroxide is a common chemical using as part of full stage chemical bleaching in pulp industrial. Kraft pulp that produced using Turi, was bleached with sodium hydroxide at 3%, 6% and 9% based on pulp weight, respectively. Unbleached pulp was served as blank test. The optical and mechanical properties of handsheet paper made from bleached kraft pulp were evaluated according to TAPPI standard. The brightness and opacity of handsheet made from bleached pulp were improved with increasing the concentration of sodium hydroxide. The mechanical properties of handsheet were improved with using 3% sodium hydroxide and gradually decreased after 3% sodium hydroxide. In conclusion, sodium hydroxide is potential to improve optical properties of Turi pulp and improve the mechanical properties of paper made from Turi pulp at certain level. Excessive usage of sodium hydroxide brings adverse effect to mechanical properties of paper made from Turi pulp.